Practices of Listening: (Re)percussions of Sound, Silences and Censorship from (Post-)Apartheid South Africa - Swinney, Warrick (Michaelis School of Fine Art, 2019)
This project is situated in the area of sonic art and explores my personal biography in relation to sound, silence, censorship and social control. Using the artistic productions of John Cage, I examine silence as both an object—a recording in a fixed medium—and as a verb directly addressing the question of censorship of the self and of others. The interplay of silencing and silence is expressed in my artistic practice which employs, as audio palate, the silences between the words of significant political speeches from South Africa. As a consequence of this process I have excised all recognizable words in various aural and video works leaving only the 'Cagean’ noise of the silence. I further examine related aspects of silence and silencing through the metaphor of the mute button—a mechanical silencing device—which serves both as a creative tool in a recording studio as well as a censorial device to prohibit voices being heard. The beating, hitting and silences are all set against a backdrop of (post) apartheid South Africa for the expression of some of my personal and theoretical realisations.